INVENTORY CONTROL OF CRITICAL SPARE PART BASED ON FNS ANALYSIS - Niken Trisnawati; Oyong Novareza; Agustina Eunike (Journal of Engineering and Management in Industrial System, 2016)
Krebet Baru I Sugar Factory is a producer of sugar that operate on the milling season that start from June until November 2015. The problem that occured in the Krebet Baru I were ineffectively and inefficiently spare parts inventory policy that cause stockout and led to production process stoppage. This research used FNS analysis for the classification spare parts and EOQ Probabilistic method for calculation of stockout probability, optimum Q and ROP,  total cost, also service level which were would be compared with existing policy. The research resulted that 44 types of spare parts categorized as urgent, 8 types else categorized as critical. EOQ Probabilistic method was chosen as the best method of control policy, with total cost reduction  by 12%-93% and service level increase by 995-100% than existing policy which resulted a total cost by Rp 5.004.890 – Rp 142.647.057 and service level by 0%-30%.